Antimicrobial effect of probiotics on bacterial species from dental plaque - Csilla Zambori; Attila Alexandru Morvay; Claudia Sala; Monica Licker; Camelia Gurban; Gabriela Tanasie; Emil Tirziu (Journal of Infection in Developing Countries)
Introduction: The antimicrobial role of probiotic Lactobacillus casei subspecies casei DG (L. casei DG) and of the mix culture of probiotic Lactobacillus acidophilus LA-5 and Bifidobacterium BB-12 was tested on species of Staphylococcus, Streptococcus, Pasteurella, and Neisseria genera from supragingival sites from dogs with dental disease of different breed, age, sex, weight, and diet. The research was conducted on these four genera because of their importance in zoonotic infections after dog bites. Methodology: Species from Staphylococcus, Streptococcus, Pasteurella, and Neisseria genera were isolated and identified. To test the antimicrobial efficacy of L. casei DG and the mixed culture of probiotic L. acidophilus LA-5 and Bifidobacterium bifidum BB-12 on the pathogenic species, the agar overlay method was used. Results: L. casei DG had a bactericidal effect on all analyzed species isolated from Staphylococcus, Streptococcus, Pasteurella, and Neisseria genera after 24 hours of incubation. The mixed probiotic culture made up of L. acidophilus LA-5 and Bifidobacterium BB-12 species had no bactericidal effect on the species of Staphylococcus and Streptococcus genera, which were resistant. However, it had a bacteriostatic effect on several species of Pasteurella and Neisseria genera. Conclusions: This work highlights the antimicrobial potential of probiotics in vitro, demonstrating that the probiotic L. casei DG has a bactericidal effect on all analyzed species isolated from dental plaque and that the mix culture of probiotic L. acidophilus LA-5 and Bifidobacterium BB-12 has only a bacteriostatic effect.